ICT Society STEM Kit - Mohamad Fauzai, Nur Anis Masturah; Yahaya, Aini Fazihah; Kassim, Kamalina; Mohd Naser, Fathin Nur Balqis; Azman, Nurul Hanani; Mat Sout, Norhisyam; Azman, Hazeeq Hazwan (Multidisciplinary Applied Research and Innovation, 2021)
Computational skill should be emphasized while strategically integrating the “Internet of Things” in education to prepare future workforce for the challenges ahead. Therefore, the curriculum content would have to be updated to develop students’ understanding of the nature and advantages of Industrial Revolution 4.0 along with relevant modules to assist STEM education in the area of Information and Communications Technology (ICT). A major challenge to increasing exposure is the number of students taking Science, Technology, Engineering and Mathematics (STEM) subjects is declining annually. The popular reason of fewer students interested in STEM is because they tend to choose subjects that are much easier or they could not see how science can play a role in their lives. Thus, a game-based learning approach could facilitate in promoting STEM interest among students while inculcating the fundamental knowledge of ICT and its importance in daily life. ICT Society kit is developed with the objectives in tackling this issue. This kit comprises of two activities focusing on binary coding and logical thinking. A pilot study conducted in two rural schools in Kuala Selangor, totaling 47 participants, demonstrated this kit resulted in the participants gaining STEM skills including critical thinking, innovativeness, problem-solving, and decision making. There is a lack of Malaysian ICT STEM kits which can be conducted offline without the need of computer. This ICT Society kit is unique, mobile, affordable and most importantly, easily applied in a rural school setting. ICT Society kit offers great potential for commercialization and upscaling the production of this kit will allow outreach towards a larger crowd. This kit could inspire younger generations to pursue STEM fields, which is important to create a smarter and innovative society.